2022
DOI: 10.3390/ijerph19073912
|View full text |Cite
|
Sign up to set email alerts
|

Under Pressure: The Chronic Effects of Lower-Body Compression Garment Use during a 6-Week Military Training Course

Abstract: Background: Previous studies have shown that compression garments may aid recovery in acute settings; however, less is known about the long-term use of compression garments (CG) for recovery. This study aimed to assess the influence of wearing CG on changes in physical performance, subjective soreness, and sleep quality over 6 weeks of military training. Methods: Fifty-five officer-trainees aged 24 ± 6 y from the New Zealand Defence Force participated in the current study. Twenty-seven participants wore CG eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
(48 reference statements)
0
6
2
Order By: Relevance
“…The findings we present are the first to report deleterious effects from CG on muscular adaptation, contradicting previous findings which suggest variable, but likely positive effects on strength, power and endurance outcomes (Baum et al, 2020;Edgar et al, 2022).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The findings we present are the first to report deleterious effects from CG on muscular adaptation, contradicting previous findings which suggest variable, but likely positive effects on strength, power and endurance outcomes (Baum et al, 2020;Edgar et al, 2022).…”
Section: Discussioncontrasting
confidence: 99%
“…The findings we present are the first to report deleterious effects from CG on muscular adaptation, contradicting previous findings which suggest variable, but likely positive effects on strength, power and endurance outcomes (Baum et al., 2020 ; Edgar et al., 2022 ). However, the adaptations underpinning RBE are likely distinct from those elicited by either hypertrophy or endurance training (Hyldahl et al., 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, future studies can investigate the long-term effects of repetitive training protocols with compression garments on exercise performances. Perhaps, long-term training with compression garments may prevent the overuse of muscles and joints and athletic injuries presumably facilitating the efficacy of training programs [82]. Further, despite the potential advantages of compression garments with respect to neurophysiological, biomechanical, or perceptual components, how these improvements in the motor system support specific exercise performances is still inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies were identified and grouped within the 'Musculoskeletal disorders' outcome domain [50][51][52][53][54]. Three interventions were coded as 'Physiological modificationssupport/compression', 1 intervention was coded as 'Physiological modifications-mixed physical training' and 1 intervention was coded as 'Multifaceted'.…”
Section: Musculoskeletal Disordersmentioning
confidence: 99%